Employment status and HIV viral load in Chilean adult population: a propensity score analysis - Leiva-Escobar, Ignacio; Cortes, Claudia P.; Lamadrid, Angelo (Aids and behavior, 2025)
We set out to investigate the potential impact of unemployment on HIV viral load in individuals living with HIV at the biggest HIV-related healthcare centre in Chile. We analysed a cross-sectional dataset of 803 adults living with HIV on antiretroviral therapy. The main exposure was employment status. The outcome, detectable HIV viral load, was operationalised using a cut-off of HIV viral load at 20 copies/mL. We applied a propensity score method, the inverse probability of treatment weighting to control for measured confounders. We found that 219 (27.3%) of participants were unemployed. Being unemployed was associated with increased odds of being detectable (OR = 1.78, 95%CI = 1.18-2.71) compared to being employed. Additionally, we found that those unemployed and non-adherents have higher odds of being detectable (OR = 2.53, 95%CI = 1.18-5.41). Unemployment status may influence HIV viral load. However, further research is needed to determine and understand the social structure behind those relationships in the Chilean people living with HIV.